Development of a promotional media model using puzzle media as an effort to increase knowledge of dental and oral health maintenance in Preschool Children - Samjaji, Samjaji; Miko, Hadiyat; Widyagdo, Agung (Center of Excellent (Pusat Unggulan Iptek), 2024)
Background: Efforts to increase the knowledge of society in general and school children in particular can be carried out through the Communication, Information and Education (KIE) program. Learning while playing is an effective method for children to increase their knowledge. The media used varies greatly, from oral, singing, printed or written media, games such as snakes and ladders and puzzles, to electronic media such as television and the internet. Puzzles are an interesting game for children, because basically children like attractive colored images. Puzzles can train finger dexterity and hand-eye coordination, as well as the cognitive concept of matching shapes and parts to wholes. Objective: To determine the effect of Health Promotion using puzzle media in increasing preschool children's dental health knowledge. Method: This study used a one group pretest and posttest design by providing treatment and measuring preschool children's knowledge before and after treatment. Results: The results of the analysis obtained a significance value of <0.05. Conclusion: There is an influence of puzzle media in increasing the knowledge and dental hygiene of preschool children.